Diurnal variation in subfoveal and peripapillary choroidal vascularity index in healthy eyes - Sumit Randhir Singh; Mohammed Abdul Rasheed; Abhilash Goud; Niroj Kumar Sahoo; Kiran Kumar Vupparaboina; Jay Chhablani (Indian Journal of Ophthalmology, 2019)
Purpose: To report the diurnal variation in choroidal vascularity index (CVI) in subfoveal (SF-CVI) and peripapillary area in healthy eyes. Methods: The study was a cross-sectional study including 12 healthy subjects. Swept-source optical coherence tomography scans were taken at 9 am, 11 am, 1 pm, 3 pm, and 5 pm. Subfoveal choroidal thickness (SFCT) and CVI were calculated using automated segmentation techniques and previously validated algorithms. Systemic parameters including systolic blood pressure (SBP), diastolic blood pressure, mean arterial pressure, and mean ocular perfusion pressure were calculated and correlated with SFCT and CVI. Results: A total of 12 eyes (right eye) of 12 patients (mean age: 26 ± 3.77 years) were analyzed. The mean (±standard deviation) amplitude of SFCT and SF-CVI variation was 35.91 ± 14.8 μm (range, 15–69 μm) and 0.05 ± 0.02 (range, 0.02–0.08). The mean CVI showed a significant diurnal variation in the temporal quadrant of the peripapillary region (P = 0.02). Conclusion: SFCT and SF-CVI showed a significant diurnal variation in amplitude (peak–trough analysis) and SF-CVI correlated well with SBP suggestive of a direct influence of blood pressure on choroidal vascularity. The mean peripapillary CVI in the temporal quadrant also showed a significant diurnal variation with no significant change in other quadrants.